Bullying In the School Environment: A Thematic Analysis of Causes, Consequences, and Prevention Efforts - Alya Maisarah Binti Dahlan (Lembaga Pengembangan Kinerja Dosen, 2026)
The goal of this thesis is to increase awareness and give victims a better understanding of the causes of bullying and coping mechanisms by analysing the causes, effects, and efficacy of current anti-bullying interventions at Cendekia Harapan School in Jimbaran, Bali. To strengthen anti-bullying initiatives, it also assesses current solutions and makes culturally appropriate suggestions. Students completed open-ended surveys as part of a qualitative research design to learn more about their individual experiences, opinions, and the success of ongoing programs. To find patterns in bullying behaviours and their impacts, thematic analysis was used. The results showed that bullying is frequently caused by insecurity, a desire for power, and a need to fit in. Bullying victims often experience emotional distress, mental health conditions like anxiety and depression, and academic decline. According to the study, bullying can be influenced by the school environment. While students believe that current initiatives are effective, they also recommend additional interventions like workshops that foster empathy and greater parental involvement. These findings provide useful recommendations for improving school-based anti-bullying initiatives and corroborate theories put forth by Olweus and Adler.